2024
DOI: 10.3390/ijms25020923
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Effects of the Garlic Organosulfide Diallyl Trisulfide through the Attenuation of B[a]P-Induced Oxidative Stress, AhR Expression, and DNA Damage in Human Premalignant Breast Epithelial (MCF-10AT1) Cells

Dominique T. Ferguson,
Equar Taka,
Syreeta L. Tilghman
et al.

Abstract: Benzo[a]pyrene (B[a]P) is the most characterized polycyclic aromatic hydrocarbon associated with breast cancer. Our lab previously reported that the organosulfur compound (OSC), diallyl trisulfide (DATS), chemoprevention mechanism works through the induction of cell cycle arrest and a reduction in oxidative stress and DNA damage in normal breast epithelial cells. We hypothesize that DATS will inhibit B[a]P-induced cancer initiation in premalignant breast epithelial (MCF-10AT1) cells. In this study, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Similarly, in in vitro research, DATS (diallyl trisulfide), constituents of allicin, have indicated potential to suppress carcinogenic activity in normal and cancerous breast cells via inducing apoptosis and cell cycle arrest. Additionally, they tend to repress cell proliferation and oxidative DNA damage [ 93 ].…”
Section: Allicin and Cancer Hallmarksmentioning
confidence: 99%
“…Similarly, in in vitro research, DATS (diallyl trisulfide), constituents of allicin, have indicated potential to suppress carcinogenic activity in normal and cancerous breast cells via inducing apoptosis and cell cycle arrest. Additionally, they tend to repress cell proliferation and oxidative DNA damage [ 93 ].…”
Section: Allicin and Cancer Hallmarksmentioning
confidence: 99%